Efficient functionalization of alginate biomaterials. (February 2016) - Dalheim, Marianne Ø.; Vanacker, Julie; Najmi, Maryam A.; Aachmann, Finn L.; Strand, Berit L.; Christensen, Bjørn E.
Abstract: Peptide coupled alginates obtained by chemical functionalization of alginates are commonly used as scaffold materials for cells in regenerative medicine and tissue engineering. We here present an alternative to the commonly used carbodiimide chemistry, using partial periodate oxidation followed by reductive amination. High and precise degrees of substitution were obtained with high reproducibility, and without formation of by-products. A protocol was established usingl -Tyrosine methyl ester as a model compound and the non-toxic pic-BH3 as the reducing agent. DOSY was used to indirectly verify covalent binding and the structure of the product was further elucidated using NMR spectroscopy. The coupling efficiency was to some extent dependent on alginate composition, being most efficient on mannuronan. Three different bioactive peptide sequences (GRGDYP, GRGDSP and KHIFSDDSSE) were coupled to 8% periodate oxidized alginate resulting in degrees of substitution between 3.9 and 6.9%. Cell adhesion studies of mouse myoblasts (C2C12) and human dental stem cells (RP89) to gels containing various amounts of GRGDSP coupled alginate demonstrated the bioactivity of the material where RP89 cells needed higher peptide concentrations to adhere.